2004
DOI: 10.1007/s11172-005-0041-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymers containing phenylquinoxaline rings

Abstract: The synthesis and properties of poly(phenylquinoxalines) containing hexafluoroiso propylidene or silylene units in the backbone are described. The polymers have been prepared by polycondensation of aromatic diamines containing preformed phenylquinoxaline rings with a dianhydride or diacid chlorides containing hexafluoroisopropylidene groups, or with a dianhydride or diacid chlorides containing silylene units. The solubility, thermal stability, film forming ability, and electric insulating, mechanical, and elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…They are processed using the intermediate polyamidic acids which are soluble in certain solvents and can be cast into thin films from such solutions followed by a thermal treatment which renders the insoluble polyimides. Due to this processing technology aromatic polyimides can be successfully used as thin films, coatings and adhesives in microelectronics, as membrane materials in transport membrane industry, or in other advanced fields [1][2][3][4]. For this purpose, it would be very interesting to design the structure of the repeating unit in such a way that the corresponding polymer will have the most convenient physical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…They are processed using the intermediate polyamidic acids which are soluble in certain solvents and can be cast into thin films from such solutions followed by a thermal treatment which renders the insoluble polyimides. Due to this processing technology aromatic polyimides can be successfully used as thin films, coatings and adhesives in microelectronics, as membrane materials in transport membrane industry, or in other advanced fields [1][2][3][4]. For this purpose, it would be very interesting to design the structure of the repeating unit in such a way that the corresponding polymer will have the most convenient physical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported that PAs containing quaternary silicon atoms, specially dialkyl‐diphenylsilane moiety (‐Ph‐SiR 1 R 2 ‐Ph‐), shows improved solubility in common organic solvents, facilitating their handling and work‐up 7–18. Additionally, the introduction of CSi bonds, maintains or increases the thermal stability of PA due to the ionic character of the CSi bond.…”
Section: Introductionmentioning
confidence: 99%
“…Table I shows the thermal decomposition temperatures (TDT), taken as the temperature at which the weight loss is 10%, and figure 3 the thermogravimetric curves. It has been reported that the bond polarity has influence on the thermal stability, in the sense that when the chain polarity increases, the thermal stability also increases (4). In this case, the only difference between the PIAs is the nature of the heteroatom.…”
Section: Figure 2 Dsc Curves Of the Poly(imide-amides)mentioning
confidence: 99%
“…Bruma et al have reported that the presence of C-Si bonds can improve the solubility of the polymers due to the ionic character of this bond (4). Other effect of the introduction of C-Si or C-Ge bonds in a polymeric chain is the possible increasing of the thermal stability due to the ionic character of these bonds.…”
Section: Introductionmentioning
confidence: 99%